If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2x + -5 = 4x + -6 Reorder the terms: -5 + x + 2x = 4x + -6 Combine like terms: x + 2x = 3x -5 + 3x = 4x + -6 Reorder the terms: -5 + 3x = -6 + 4x Solving -5 + 3x = -6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + 3x + -4x = -6 + 4x + -4x Combine like terms: 3x + -4x = -1x -5 + -1x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + -1x = -6 + 0 -5 + -1x = -6 Add '5' to each side of the equation. -5 + 5 + -1x = -6 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = -6 + 5 -1x = -6 + 5 Combine like terms: -6 + 5 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| 97=12n | | 7/8×50×9/11×15 | | 0=5x^2-x | | -3/-5=7 | | 3x^2+19x+13=0 | | y=x-x+y | | 7=7y+4(y+7) | | 6m^2-26=-m | | 6y+6x=5y+2x | | 4[2t-4]= | | y-1=-7(x+4) | | 12-8t=-52 | | y-2=.16666(x-6) | | -5-2m=9 | | 7(6m-6)+3=-81 | | 8t-16= | | 2x+8=14x+12 | | y=t+t-y | | 3(-40+-2r)+20= | | y-2=.10(x+10) | | 2•-4/5 | | 6-4(2x+8)=16 | | (t-3)7=6+21 | | 6x-13=90 | | 8[t-2]= | | 4v+4=4 | | 4p+1=-15 | | 4k-3(k-8)=2(3-5k)+7 | | 50-5x=80-17x | | 15y-(3-[4y+4]+57)=2-y | | 2(6-4x)=21-9x | | -7+(8z+2)=(7z+5)+1 |